2015
DOI: 10.1002/mrm.25899
|View full text |Cite
|
Sign up to set email alerts
|

Correcting heat‐induced chemical shift distortions in proton resonance frequency‐shift thermometry

Abstract: Purpose To reconstruct proton resonance frequency (PRF)-shift temperature maps free of chemical shift (CS) distortions. Theory and Methods Tissue heating created by thermal therapies such as focused ultrasound surgery (FUS) results in a change in PRF that causes geometric distortions in the image and calculated temperature maps, in the same manner as other CS and off-resonance distortions if left uncorrected. We propose an online-compatible algorithm to correct these distortions in 2DFT and EPI acquisitions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…The off‐resonance‐induced shifting artifacts observed in this work were largely a result of a mismatch of the center frequencies across the three orthogonal imaging planes caused by differences in magnetic susceptibility from the water volume, and, to a lesser extent, due to heating of the focal volume . Although the magnitudes of the spatial shifts were only about 1–2 mm in most cases, this level of misalignment cannot be ignored when lesions on the order of 5 mm in size are considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The off‐resonance‐induced shifting artifacts observed in this work were largely a result of a mismatch of the center frequencies across the three orthogonal imaging planes caused by differences in magnetic susceptibility from the water volume, and, to a lesser extent, due to heating of the focal volume . Although the magnitudes of the spatial shifts were only about 1–2 mm in most cases, this level of misalignment cannot be ignored when lesions on the order of 5 mm in size are considered.…”
Section: Discussionmentioning
confidence: 99%
“…However, proper calculation of the ATD during clinical MRgFUS treatments raises several technical challenges. For instance, because MR‐thermometry is typically carried out in multiple orthogonal two‐dimensional planes (i.e., axial, coronal, sagittal) throughout the procedures using different frequency encoding directions and a fixed center frequency, spatial misalignments of the measured heating areas can arise due to artifacts caused by off‐resonance . A PubMed search performed on Oct 5 2017 with the terms: “accumulated thermal dose”, “human,” and “brain” suggested that no data regarding the ATD required for in vivo brain tissue ablation in humans have been reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…Informed consent and approval from the Institutional Review Board at Stanford University was obtained before the treatment. To ablate a soft tissue tumor in the leg, MR‐guided sonications were performed at 3T (Signa, GE Healthcare, Milwaukee, WI; ExAblate 2000, Insightec Ltd., Haifa, Israel) with 12 ms TE, 25 ms TR, 280 × 280 mm 2 FOV, 256 × 256 matrix size, 10 time frames, 95 slices, 5 mm slice thickness, and 44 Hz pixel BW . Reconstructed temperature images were further processed to calculate a thermal dose map in cumulative equivalent minutes (CEM) …”
Section: Methodsmentioning
confidence: 99%
“…However, direct subtraction of image phase is prone to errors resulting from spatiotemporally varying sources of distortion, including off‐resonance, tissue motion, and respiration. Many approaches have been reported that make PRFS thermometry more robust to these sources of error . Another challenge is the presence of fat in heated voxels, since fat experiences a much smaller PRFS with temperature than water .…”
Section: Introductionmentioning
confidence: 99%
“…Many approaches have been reported that make PRFS thermometry more robust to these sources of error. [2][3][4][5][6][7][8] Another challenge is the presence of fat in heated voxels, since fat experiences a much smaller PRFS with temperature than water. 9 This is particularly a problem when monitoring therapies such as focused ultrasound ablation of breast tumors, which are highly embedded in adipose tissue.…”
mentioning
confidence: 99%